KESALAHAN DIKSI DAN KALIMAT PENGISI SUARA ACARA INFOTAINMENT INSERT - Lili Suryaningsih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This study described errors of the dubbers in the infotaiment issues in the INSERT program presented by Trans TV channel, focusing on diction and sentence variations used by the host.  Problem addressed in this study was to what extents accuracy and accuratness in the words and sentences used by the host met criteria of good and correct Bahasa Indonesia. This study used content analysis with qualitative approach. Data were derived from document analysis obtained from the records of the INSERT program from 1-8 December 2016.  This study concluded that some language errors occured in the selection of words, phrases and sentences, implying meanings in the news was bias, misinterpreted even misled for the audiences. Instead of giving negative impact as an issue or rumor, the news was perceived as propaganda or black campaign.